A novel integrated framework for securing online instructor-student communication. (2019) - Salem, Maher; Samara, Khalid; Aldhaheri, Mohammed Saeed
Academic advising is a time-consuming effort in educational institutions. Advising and consulting students are critical, which can cause latency and additional overhead for both the instructor and student. This paper proposes an effective and secured online framework to enrich the advising experience between the instructor and student and enhance time management. It provides two main services: reserved time slots for each student and common discussion between students and instructors. Reserving a time slot means that the student can communicate with the advisor anywhere. It can start an embedded web-based virtual machine to interact with the instructor in real time. The second service is to share a general post with all students and instructors to come up with a generic solution. Security plays a dominant role in the framework. It uses a strong authentication mechanism and encrypts the entire traffic to keep the data confidential.